In vitro anticancer potential of Manilkara hexandra (Roxb.) leaf methanolic extracts via SRB and MTT assays against MCF-7 cell line - Sunayana R. Vikhe; Sarika Vikhe; Vaibhav Bhamare (Creative Pharma Assent, 2025)
Background: Cancer causes millions of deaths worldwide, with cases expected to reach 28.4 million by 2040. Natural plant compounds offer safer alternatives for cancer treatment. Aim: This study tested the anticancer activity of Manilkara hexandra leaf extracts against MCF-7 breast cancer cells. Materials and methods: Methanolic extraction, followed by sequential fractionation via column chromatography, yielded bioactive fractions that underwent phytochemical and GC-MS characterization. Quantification of cytotoxicity was performed using sulforhodamine B (SRB) and 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays across a concentration gradient (10–80 μg/mL). Result and Discussion: Chemical screening found alkaloids, flavonoids, tannins, and other bioactive compounds. The petroleum ether-ethyl acetate (PE-EA) fraction contained quercetin (25.28%) and another major flavonoid (28.62%). This fraction exhibited strong dose-dependent cell killing, reducing cell survival to 31.8% (SRB) and 33.0% (MTT) at 80 μg/mL (p < 0.001). The IC₅₀ was 55 μg/mL in both assays. Conclusion: The anticancer activity correlates with high flavonoid content, suggesting these compounds cause cell death through apoptosis or cell cycle arrest. M. hexandra PE-EA fraction shows promise as a natural anticancer agent for breast cancer treatment